1950
DOI: 10.1103/physrev.78.629
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Ray Spectrum ofK40

Abstract: I N a previous communication 1 the results of a spectrometer measurement on K 40 beta-rays were presented. The source was KC1, 18.5 rag/cm 2 in thickness, enriched to 1.2 percent K 40 , giving a maximum yield less than background. The end point occurred at 1.40±0.03 Mev and the apparent shape was that of an allowed type spectrum above 500 kev. Such a shape is in contradiction to the theory of forbidden beta-decay and the predictions of Marshak 2 for K 40 . Since the known spin change is 4, Marshak showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1950
1950
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…[38][39][40][41], the shapefactor function CðW Þ ¼ q 6 þ 7ðp 4 q 2 þ p 2 q 4 Þ þ p 6 estimated theoretically for the third forbidden unique transitions agrees well with the data obtained by experiment. However, a careful study of the Kurie plot linearizations reported in these references reveals a considerable deviation between theory and experiment below 500 keV.…”
Section: Article In Presssupporting
confidence: 77%
See 2 more Smart Citations
“…[38][39][40][41], the shapefactor function CðW Þ ¼ q 6 þ 7ðp 4 q 2 þ p 2 q 4 Þ þ p 6 estimated theoretically for the third forbidden unique transitions agrees well with the data obtained by experiment. However, a careful study of the Kurie plot linearizations reported in these references reveals a considerable deviation between theory and experiment below 500 keV.…”
Section: Article In Presssupporting
confidence: 77%
“…The observed tendency is in agreement with the Kurie plot extrapolations reported in Refs. [38,39,41]. When comparing the curves with each other, the yield curve computed for E 0 ¼ 1360 keV agrees better with the values obtained by experiment when E4800 keV, whereas the curve 40 K, (c) 10 Be with the values obtained by experiment.…”
Section: Article In Presssupporting
confidence: 66%
See 1 more Smart Citation